14 POST-HOC ANALYSIS OF TOFACITINIB CROHN'S DISEASE PHASE 2 INDUCTION EFFICACY IN SUBGROUPS WITH BASELINE ENDOSCOPIC OR BIOMARKER EVIDENCE OF INFLAMMATION. (18th January 2018) - Sands, Bruce E; Panés, Julian; Higgins, Peter D R; Moscariello, Michele; Chan, Gary; Su, Chinyu; Wang, Wenjin; Maller, Eric
Abstract: Background: Tofacitinib is an oral, small molecule Janus kinase (JAK) inhibitor that is being investigated for IBD. In a recent trial of Crohn's disease (CD) patients (pts), small treatment effects for tofacitinib vs placebo (PBO) were noted using CD Activity Index (CDAI)-based enrollment criteria without endoscopic scoring (1). We report post-hoc analyses of efficacy endpoints (CDAI-based and composite outcomes) in subgroups based on objective baseline (BL) criteria of disease activity. Methods: In a randomized, double-blind, PBO-controlled multicenter Phase 2b trial (NCT01393626), pts with moderate to severe CD (CDAI 220–450) received PBO, tofacitinib 5 or 10mg twice daily (BID) for 8 weeks. Clinical remission (CDAI <150), clinical response 100 (≥100 CDAI reduction from BL), composite remission (remission and ≥50% C-reactive protein [CRP] or fecal calprotectin [FCP] reduction from BL) and composite response (CDAI-100 response and ≥50% CRP or FCP reduction from BL) were analyzed at Week 8, by subgroups defined by BL simple endoscopic score (SES) <11 (median 11; local read), SES ≥11 or biomarkers (CRP ≥5mg/L or FCP ≥250mg/kg). Results: In pts with BL SES ≥11, significantly higher proportions achieved remission, composite remission and composite response with tofacitinib vs PBO (all p<0.05 except clinical remission with tofacitinib 5mg BID; Table). Observations were similar in pts with BL CRP ≥5 or FCP ≥250. Pts with BL SES <11 had significantly higher rates of composite remission and composite response with tofacitinib vs PBO (all p<0.05 except composite remission with tofacitinib 5mg BID). Conclusion: Increased proportions of pts were in remission and achieved composite remission and composite response with tofacitinib vs PBO, when analyses were done using more objective BL criteria of active disease than simple measure of CDAI. Results from these post-hoc analyses support further investigation of JAK inhibition in CD. 1. Panés J, et al. Gut 2017;66:1049–59